Evaluating a structured expert elicitation approach for adaptive conservation management based on lessons from five years in practice - Helen J. Mayfield; James Brazill‐Boast; Mick Andren; Michiala Bowen; Adam Fawcett; Trent Forge; Luke Foster; Ross Goldingay; Paul Hillier; Meagan Hinds; Simon Lee; Erica Mahon; et al. (Conservation Biology, 2026)
Adaptive management of threatened species relies on having ex ante estimates of species’ responses to different interventions. Structured expert elicitation is often used to generate these estimates, but comparisons of these expert‐predicted outcomes with observed results are rare. This study aims to evaluate the utility of expert elicitation for adaptive management in the New South Wales Saving our Species program in Australia by revisiting six species management plans that were generated from tailored structured elicitation guidelines developed five years prior. Each species’ management plan included a defined scope, conceptual model, monitoring indicators, and estimated response to management curves under different scenarios. Experts reviewed the conceptual models after five years of management and compared the predicted response to management with observed monitoring data. In three of the six case studies, observed outcomes closely matched predictions. Where predictions diverged, factors such as unanticipated new threats and unexpected responses to interventions potentially contributed to discrepancies. However, in all cases, the structured approach provided a clear logic for planning, enabling managers to systematically refine their understanding. The conceptual models and response curves were valuable for collaborating, communicating, and generating hypotheses for unexpected results. This work demonstrates the value of tailored guidelines in supporting adaptive management processes and showcases the value of documenting expert knowledge in management settings with high uncertainty.

The smell of Panulirus argus virus 1 (PaV1) infection: Disease-induced changes in metabolites in urine and hemolymph of Caribbean spiny lobsters Panulirus argus - Boyu Qin; Donald Behringer; Abigail K. Scro; Erica Ross; Hajime Uchida; Satoshi Yoshimura; Jan Tebben; Tilmann Harder; Charles Derby; Michiya Kamio (Journal of Invertebrate Pathology, 2026)

Understanding Motivators and Challenges to Enrollment in Maternal and Child Health and Nutrition Research: A Mixed Methods Study with Women of Child-Bearing Age and Clinical Practitioners - Alexandra MacMillan Uribe; Rebecca Seguin Fowler; Kelly Fisher; Erica Bender; Galen Eldridge; Margaret Demment; Regan Bailey; A. Catharine Ross; Diane Mitchell; Sarah Ray; Julie Gras-Najjar; Alexandra Early (Journal of Nutrition Education and Behavior, 2025)

Exploring the consequences of introducing alternative fishing gear in an effort-limited fishery: Casita utilization in the spiny lobster, Panulirus argus, fishery in Florida - Gabrielle F. Renchen; Erica P. Ross; Thomas R. Matthews (Fisheries Research, 2025)

Bioeconomic modeling of on-growing Caribbean spiny lobster in Florida - Taryn Garlock; Frank Asche; Casey B. Butler; Sherry Larkin; Thomas R. Matthews; Erica Ross (Aquaculture, 2025)

Reflex impairment as a predictor of mortality in Panulirus argus: Implications for the live export market - Erica P. Ross; Casey B. Butler; Carly M. Hannah; Thomas R. Matthews (Fisheries Research, 2024)

Gastric mill ossicles record chronological age in the Caribbean spiny lobster (Panulirus argus) - Emily Hutchinson; Thomas R. Matthews; Erica Ross; Samantha Hagedorn; Mark J. Butler (Fisheries Research, 2024)

Price variation in the Caribbean spiny lobster fishery: Incentives for ongrowing wild-caught lobsters in Florida - Taryn Garlock; Frank Asche; Casey B. Butler; Thomas R. Matthews; Erica Ross (Fisheries Research, 2024)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Species‐specific responses to climate change and community composition determine future calcification rates of Florida Keys reefs - Remy R. Okazaki; Erica K. Towle; Ruben van Hooidonk; Carolina Mor; Rivah N. Winter; Alan M. Piggot; Ross Cunning; Andrew C. Baker; James S. Klaus; Peter K. Swart; Chris Langdon (Global Change Biology, 2017)
Anthropogenic climate change compromises reef growth as a result of increasing temperatures and ocean acidification. Scleractinian corals vary in their sensitivity to these variables, suggesting species composition will influence how reef communities respond to future climate change. Because data are lacking for many species, most studies that model future reef growth rely on uniform scleractinian calcification sensitivities to temperature and ocean acidification. To address this knowledge gap, calcification of twelve common and understudied Caribbean coral species was measured for two months under crossed temperatures (27, 30.3 °C) and CO 2 partial pressures ( p CO 2 ) (400, 900, 1300 μatm). Mixed‐effects models of calcification for each species were then used to project community‐level scleractinian calcification using Florida Keys reef composition data and IPCC AR 5 ensemble climate model data. Three of the four most abundant species, Orbicella faveolata, Montastraea cavernosa, and Porites astreoides , had negative calcification responses to both elevated temperature and p CO 2 . In the business‐as‐usual CO 2 emissions scenario, reefs with high abundances of these species had projected end‐of‐century declines in scleractinian calcification of >50% relative to present‐day rates. Siderastrea siderea , the other most common species, was insensitive to both temperature and p CO 2 within the levels tested here. Reefs dominated by this species had the most stable end‐of‐century growth. Under more optimistic scenarios of reduced CO 2 emissions, calcification rates throughout the Florida Keys declined S. siderea are not already dominant. This study demonstrates how species composition influences reef community responses to climate change and how reduced CO 2 emissions can limit future declines in reef calcification.

Gene flow and the maintenance of species boundaries - Erica L. Larson; Thomas A. White; Charles L. Ross; Richard G. Harrison (Molecular Ecology, 2014)
Hybrid zones are regions where individuals from genetically differentiated populations meet and mate, resulting in at least some offspring of mixed ancestry. Patterns of gene flow (introgression) in hybrid zones vary across the genome, allowing assessment of the role of individual genes or genome regions in reproductive isolation. Here, we document patterns of introgression between two recently diverged species of field crickets. We sampled at a very fine spatial scale and genotyped crickets for 110 highly differentiated single nucleotide polymorphisms ( SNP s) identified through transcriptome scans. Using both genomic and geographic cline analysis, we document remarkably abrupt transitions (